Analisis pendapatan petani padi melalui penerapan pengendalian hama terpadu di Desa Aska Kecamatan Sinjai Selatan - Megawati, Megawati; Afiat, Husnul; Salmawati, Salmawati; Maharani, Maharani; Susanti, Susi; Ansyah, Ferdy (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2024)
Rice is an important food commodity because it is the staple food and source of income for the Indonesian population. Efforts to increase rice production continue to be implemented by the government to maintain food availability and increase farmers' income. One of the efforts made is Integrated Pest Management. The purpose of this study was to analyze the income of rice farmers through the application of Integrated Pest Management in Aska Village, South Sinjai District. The method used is a survey method conducted on 30 respondents of rice farmers who apply Integrated Pest Management. Data analysis used the calculation of income based on the value of total revenue and total cost and RCR. The results showed that rice farming with the application of Integrated Pest Management is feasible to run with a total income of Rp. 9,370,205 and with a value of RCR> 1.